Autorytet Seneki w argumentacji wczesnochrześcijańskiej - Nehring, Przemysław (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The paper deals with the authority of Seneca employed by the eminent early Christian writers in their apologetic as well as polemical works.
The Authority of Seneca in the Early Christian Argumentation
The analysis of the quotations from the works of this famous Roman philosopher and also some hints to them with a declaration of their authorship leads to the conclusion that his authority exceeded in the world of Christian literature far beyond the sphere of similarities between Stoic and Christian ethics. The early Church authors refer to Seneca almost exclusively in the dispute with the well educated opponents of Christianity who based their critics on the philosophical, very often Stoic tradition. Seneca is regarded in the circle of Christian Latin writers as the most important and almost obvious philosophical authority. Quoting his words in support of the arguments concerning various theological issues used to enhance the position in the debate.
Keywords: Seneca; Tertulian; Laktancjusz; Hieronim; Augustyn; retoryka; argumentacja